The Influence Of Individual Characteristics and Competencies on Employee Performance with Work Ethic as a Moderating Variable at The Dairi Panwaslu Office - Nurul Ampe Lestari Angkat; Mesra B; Kiki Farida Ferine; Muhammad Isa Indrawan (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of individual characteristics and competencies on employee performance, with work ethic as a moderation variable, at the Dairi Regency Panwaslu Office. This study used an associative quantitative approach with a saturated sample technique on 35 employees. Data was collected through questionnaire deployment and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software version 3.3.3. The results showed that individual characteristics did not have a significant effect on employee performance (T-Statistic = 0.452 < 1.96; P-Value = 0.654), while competence has a positive and significant effect on employee performance (T-Statistic = 3.128 > 1.96; P-Value = 0.004). Work ethic was also found to have no significant effect directly on employee performance (T-Statistic = 0.385 < 1.96; P-Value = 0.703), and did not moderate the relationship between individual characteristics and employee performance (T-Statistic = 1,300 < 1.96; P-Value = 0.202), as well as the relationship between competence and employee performance (T-Statistic = 1.053 < 1.96; P-value = 0.299). These findings show that competence is the most dominant factor in influencing employee performance, while work ethic does not strengthen the influence of individual characteristics or competencies on employee performance. Therefore, it is recommended that organizations focus efforts on improving employee competencies through technical training, regulatory understanding, and professional development programs. Further research can add other variables such as organizational culture, reward system, or leadership style to explain the variation in employee performance more comprehensively.